Analytical bond order potential for simulations of BeO 1D and 2D nanostructures and plasma-surface interactions. (5th March 2018) - Byggmästar, J; Hodille, E A; Ferro, Y; Nordlund, K
Abstract: An analytical interatomic bond order potential for the Be–O system is presented. The potential is fitted and compared to a large database of bulk BeO and point defect properties obtained using density functional theory. Its main applications include simulations of plasma-surface interactions involving oxygen or oxide layers on beryllium, as well as simulations of BeO nanotubes and nanosheets. We apply the potential in a study of oxygen irradiation of Be surfaces, and observe the early stages of an oxide layer forming on the Be surface. Predicted thermal and elastic properties of BeO nanotubes and nanosheets are simulated and compared with published ab initio data.